The Contingent Impact of Integrated Reporting on Cost of Equity: Evidence from Good Corporate Governance Moderators in Indonesia - Sia, Johanna Jono; Weli, Weli (Dinamika Akuntansi Keuangan dan Perbankan, 2026)
This study analyzes the effect of Integrated Reporting (IR) on the Cost of Equity (COE) by examining the moderating role of Good Corporate Governance (GCG) mechanisms in companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Governance quality is operationalized through two key mechanisms: institutional ownership and the proportion of independent board of commissioners. Employing Process Hayes Model 2 with bootstrap iterations of 5,000, and a final sample of 323 company-year observations after outlier removal, the study finds that Integrated Reporting does not exert a significant direct influence on Cost of Equity. However, the proportion of independent board of commissioners significantly moderates the negative relationship between Integrated Reporting and Cost of Equity, while institutional ownership fails to produce a significant moderating effect. Notably, under conditions of high institutional ownership paired with a low proportion of independent commissioners, Integrated Reporting paradoxically increases the Cost of Equity, underscoring the critical role of internal governance mechanisms in establishing the credibility of disclosed information. These findings confirm that the effectiveness of Integrated Reporting in reducing Cost of Equity is contingent upon the quality of the governance environment- particularly board independence. The study contributes to both theory and practice by demonstrating that the economic benefits of Integrated Reporting are realized only when accompanied by robust independent oversight structures.